Densified fuels from mixed plastic wastes and corn stover - Unchana Auprakul (2018)
Mixed plastic wastes recovered from dumpsites may be utilized as densified solid fuel. However, it is commonly known that plastic materials may not bind together under compaction. Corn stover can be used as natural binder in this case. It can improve chemical composition (reducing sulfur and chlorine content) and mechanical strength of the fuel pellet. In this paper, densification of mixed plastic wastes and corn stover was investigated. Compression pressure was conducted at 150 MPa. The pellet size was 8 mm in diameter and 20 mm long. Effects of moisture content (5-20%), types of material, and preheating temperatures (75 and 100°C) on the fuel properties were studied. The pellets from mixed materials were found to have higher calorific value, carbon content and durability index than corn stover pellet. © (2014) Trans Tech Publications, Switzerland.